2019
DOI: 10.1002/pbc.27868
|View full text |Cite
|
Sign up to set email alerts
|

Regional practice norms for the care of childhood cancer survivors at risk for cardiomyopathy: A Delphi study

Abstract: Background Treatment‐associated cardiomyopathy is a leading cause of morbidity and mortality for childhood cancer survivors (CCS). As evidence is not available to guide the management of CCS at risk for cardiomyopathy, we aim to describe the collective opinion of regional experts for the care of these patients using a consensus‐based Delphi methodology. Procedure Nineteen physicians from the New England region who care for CCS treated with cardiotoxic therapy (anthracyclines, thoracic radiation) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The ESC does recommend angiotensin converting enzyme inhibitors or receptor blockers (ACEI/ARB) in combination with beta-blockers in cancer survivors with symptomatic or asymptomatic cardiac dysfunction (unless contraindicated) but do not provide recommendations on other treatments [ 10 ]. A study using Delphi methodology querying physicians for their management approach of these survivors elucidated on this uncertainty, finding agreement in some areas (echocardiogram and ECG screening frequency, exercise promotion, referrals to cardiology, and use of ACEI) and disagreement in other areas (use of other cardiac testing, frequency of screening during pregnancy, and use of beta-blockers) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ESC does recommend angiotensin converting enzyme inhibitors or receptor blockers (ACEI/ARB) in combination with beta-blockers in cancer survivors with symptomatic or asymptomatic cardiac dysfunction (unless contraindicated) but do not provide recommendations on other treatments [ 10 ]. A study using Delphi methodology querying physicians for their management approach of these survivors elucidated on this uncertainty, finding agreement in some areas (echocardiogram and ECG screening frequency, exercise promotion, referrals to cardiology, and use of ACEI) and disagreement in other areas (use of other cardiac testing, frequency of screening during pregnancy, and use of beta-blockers) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This consensus‐building approach includes an iterative group survey process to achieve convergence of opinion. It is designed to identify and explore a range of alternative clinical options, to expose and explore underlying assumptions, to capture and evaluate professional opinions spanning a wide range of practice settings, and to work toward clinical consensus 6,7 . This methodology allows the investigation of clinical questions that could not practically be asked in more traditional randomized clinical trials due to the required size and cost of such a trial.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the addition of beta blockers varied between the two studies, with one survey reporting a 20% utilization rate and the other study up to 70%. Only one of the studies reported on the use of aldosterone antagonists, at approximately 50% [ 128 , 129 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%